DISTRIBUSI DAN KELIMPAHAN MAKROZOOBENTHOS DI SUNGAI SINGINGI RIAU - Rosyadi Rosyadi; Syafruddin Nasution; Thamrin Thamrin (Jurnal Ilmu Lingkungan, 2009)
This study was conducted in Singingi River in March 2008. To the objectiv of the study areidentify the macrozoobenthos community structure and its relationships with the physical andchemical properties of the river. Water and macrozoobenthos sample were taken in 3replications in 5 station namely inlower part of the river, Tanjung Pauh, Sungai Paku, Kotobaruand Petai. The samples were examined descriptively and analyzed in the labortary. Themacrozoobenthos samples were belong to 3 phylum, 4 classes, 8 families and 8 spesies. Theabundance of the organisms were 105 – 427 individu/M2, the diversity index (H’) were 0,93 –1,77, the domination index (C’) were 0,35 – 0,65 and the homogenity index were 0,52 – 0,84.The Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD), Sulphate, Ferrum,Total Suspended Solid (TSS) and Turbidity of the water were exceed the maximum levelsuggested by the Goverment Decree No. 82 / 2001, about The Management of Water Qualityand Pollution. The analysis revealed the positive correlation betwen macrozoobenthos withvarious physical and chemical characteristics of the water, the sediment and texture of thebottom material.